Risk-Returns Trade Off and Determinants of Volatility: Evidence from Malaysia - Chen, Soo Hua (2016)
Over the last few decades, there are increasing interest on risk-returns trade off. From the traditional view of risk-returns trade-off, higher risk should be compensated by higher returns. However, in recent years, it is getting more empirical studies showing the low volatility anomaly phenomenon exist in many markets regardless of developed or emerging market. This low volatility anomaly has become an international phenomenon. There are no certain conclusion on whether low volatility effect exist in emerging market. In this paper, the existence of low volatility anomaly will be examined for Malaysian stock market, KLCI. The empirical evidence shows that volatility and returns are positively related. Besides, the determinants of volatility will be analysed from the perspective of financial and accounting performance. In order to perform the panel data analysis, information of the 30 companies in KLCI covering the period from year 2004 to 2014 will be included. It includes the volatility of returns as the dependent variables and firm’s leverage, profitability, age, asset tangibility, growth rate, market capitalisation and earnings per share as the independent variables. From the result of fixed effect panel regression, firm’s leverage, profitability, age, asset tangibility and market capitalisation have negative relationship with volatility of returns. Whereas, growth rate and earnings per share have positive relationship with volatility of returns.